2021
DOI: 10.1002/ehf2.13342
|View full text |Cite
|
Sign up to set email alerts
|

All‐cause mortality predicted by peak oxygen uptake differs depending on spirometry pattern in patients with heart failure and reduced ejection fraction

Abstract: AimsIn patients with heart failure and reduced ejection fraction (HFrEF), it remains unclear how exacerbated impairments in peak exercise oxygen uptake (V O 2peak ) caused by coexistent obstructive or restrictive ventilatory defects affect mortality risk. We evaluated in patients with HFrEF, whether demonstrating either an obstructive or restrictive-patterned ventilatory defect on spirometry affects V O 2peak to yield all-cause mortality risk predicted by V O 2peak that is spirometry pattern specific. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In accordance with earlier studies, we thus confirmed that reduced pVO 2 and increased VEVCO 2 slope seem to be strongly and independently predictive of MACE in ATTR-CA patients [5][6][7]9,10]. In addition, we also found that the presence of a restrictive spirometry pattern was associated with increased MACE risk in ATTR-CA, consistent with other authors reporting that the presence of a restrictive ventilatory pattern is predictive of all-cause and cardiovascular mortality [11][12][13]. Indeed, spirometry parameters can predict outcomes and improve risk stratification based on pVO 2 in chronic heart failure patients with reduced ejection fraction [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with earlier studies, we thus confirmed that reduced pVO 2 and increased VEVCO 2 slope seem to be strongly and independently predictive of MACE in ATTR-CA patients [5][6][7]9,10]. In addition, we also found that the presence of a restrictive spirometry pattern was associated with increased MACE risk in ATTR-CA, consistent with other authors reporting that the presence of a restrictive ventilatory pattern is predictive of all-cause and cardiovascular mortality [11][12][13]. Indeed, spirometry parameters can predict outcomes and improve risk stratification based on pVO 2 in chronic heart failure patients with reduced ejection fraction [13].…”
Section: Discussionsupporting
confidence: 92%
“…While being a safe and useful diagnostic tool in many pathological conditions, CPET requires sophisticated and expensive devices, as well as specialized medical staff, which may limit its clinical use, notably in low-resource settings. In contrast, spirometry is a simple method to evaluate pulmonary function, which is successfully used to stratify heart failure severity [11][12][13]. The use of spirometry to screen for ventilatory defects in patients with heart failure is known to improve risk stratification based on pVO 2 [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct prognostic utility of spirometry is less clear among waitlisted patients [49]. However, severe intrinsic pulmonary disease with forced expiratory volume in 1 second <40% of predicted, forced vital capacity <50% of predicted, or diffusion capacity of carbon dioxide <40% are considered contraindications to heart transplantation [3,50]. The referral of such patients for simultaneous heart-lung combined transplantation at select centers may be beneficial.…”
Section: Intrinsic Lung Diseasementioning
confidence: 99%
“…More recent studies demonstrate that the V A measurement is a correlate of peak exercise oxygen uptake (V˙ o 2peak ),6 and the association between V˙ o 2peak and mortality risk is directly impacted by spirometry phenotype 7. Demonstrating that there is prognostic value associated with the V A measurement could further improve the clinical interpretation of V˙ o 2peak .…”
mentioning
confidence: 99%